PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP SISWA MELALUI PENDEKATAN MATEMATIKA REALISTIK DI SMP SWASTA TARBIYAH ISLAMIYAH - Sri Yunita Ningsih (Universitas Islam Sumatera Utara, 2017)
This study aims to determine the increase in the understanding of concepts and students ability at SMP Swasta Tarbiyah Islamiyah for the cube and beam through mathematical realistic approach. To find out how much improvement is obtained, students were given a test of understanding of concepts ability. Increased capabilities were first analyzed by using the normalized gain and processed by using two ways ANOVA formula. Two ways ANOVA formula is also used to determine whether an interaction between learning approach and students abilitiy to increase understanding of concepts skills. The results showed that (1) an increase in the understanding of concepts that students taught through mathematical realistic approach higher than understanding of concepts ability that students are taught only through ordinary learning, and (2) there is no interaction between the learning approach and the students ability to the improvement of students 'mathematical understanding of concepts ability.